The Rheological Studies on Poly(vinyl) Alcohol-Based Hydrogel Magnetorheological Plastomer - Hapipi, Norhiwani Mohd (Polymers (Basel), 2020)
The freezing–thawing method has been commonly used in the preparation of polyvinyl alcohol hydrogel magnetorheological plastomer (PVA HMRP). However, this method is complex and time consuming as it requires high energy consumption and precise temperature control. In this study, PVA HMRP was prepared using a chemically crosslinked method, where borax is used as crosslinking agent capable of changing the rheological properties of the material. Three samples of PVA HMRP with various contents of carbonyl iron particles (CIPs) (50, 60, and 70 wt.%) were used to investigate their rheological properties in both steady shear and dynamic oscillation modes. Results showed the occurrence of shear thickening behaviour at low shear rate (γ > 1 s(−1)), where the viscosity increased with the increased of shear rate. Moreover, the storage modulus of the samples also increased increasing the oscillation frequency from 0.1 to 100 Hz. Interestingly, the samples with 50, 60 70 wt.% of CIPs produced large relative magnetorheological (MR) effects at 4916%, 6165%, and 10,794%, respectively. Therefore, the inclusion of borax to the PVA HMRP can offer solutions for a wide range of applications, especially in artificial muscle, soft actuators, and biomedical sensors.